JURNALISTIK SIARAN RADIO MANDIRI FM DALAM PROGRAM TALKSHOW PSIKOLOGI ANAK - AFNAL, LIDYA; ", SUYANTO (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In the era of globalization and technology radio is as a electronic media are useful and needed by the public as a informed. One of the programs on the radio talk show which is the media as a problem solver (to guide, educate) the public about the problems of daily life. Talk show programs that have information and based on educational for society to be intelligent and open minded than be advanced society. MandiriFM radio as one of mass media that comes with child psychology talk show program News and Bussines radio in Pekanbaru. In addition, certain information contained in the application in radio journalism. The application of the course program which will support the talk show. This study aims to determine how journalism talk show program MandiriFM radio in child psychology and to find out how the process of making child psychology programs in talk show MandiriFM radio Pekanbaru.The experiment was conducted in Pekanbaru MandiriFM radio that lasted for three months from February to April 2013. This research uses descriptive qualitative method of data collection techniques of observation, interviews and documentation. This research has 14 informans which consist of 6 persons from MandiriFM Radio Pekanbaru, 3 resource persons, and 5 listeners in Talkshow Child Psychology program. Analysis using the model of Interactive Data Analysis with Miles and Huberman collecting data obtained is then processed to be reduced, so that the resulting presented a general conclusion.The results of this study indicate that the presence of broadcast journalism radio talk shows on child psychology. Among the application of radio journalism that there has been no news talk show program planning such as the determination of the topic, the existence of coverage, for the selection of data and write a script and talk show talk show program evaluation in the child psychology. In addition, there are also children's programming on the radio talk show psychology MandiriFM Pekanbaru. among them there are program planning, production and procurement program, execution program, and program of monitoring and evaluation.Keyword: radio, program, talkshow, jurnalism radio, production program